KONSEP DASAR PERILAKU DAN BUDAYA ORGANISASI: KAJIAN STRUKTUR DAN ANATOMI ORGANISASI - Nursyahbani Chusnul Novita; Tiara Lestari; Amna Idris Abdullah Khater; Zuhdiyah; Irja Putra Pratama (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research examines the basic concepts of organizational behavior and culture by focusing on organizational structure and anatomy as key elements in improving organizational effectiveness. Organizational structure serves as a formal framework for the division of tasks, authority, and responsibilities, while organizational anatomy includes communication flows and interdepartmental interactions. This study employs a literature review method by analyzing relevant books and scholarly articles. The findings indicate that organizational structure and anatomy influence individual behavior and organizational culture. The appropriate application of organizational structure, supported by effective specialization, coordination, and decision-making, can enhance organizational performance, particularly in responding to the challenges of the digital era.